1987
DOI: 10.1111/j.1095-8649.1987.tb05783.x
|View full text |Cite
|
Sign up to set email alerts
|

Composition and ultrastructure of elasmobranch granulocytes. II. Rays (Rajiformes)

Abstract: The blood granulocyte composition of seven species of ray is given together with ultrastructural observations made on the epigonal organ and blood of Puroraja spiniyera and the spleen of a deepwater rajid skate. Under the light microscope three granulocyte types, eosinophils, eosinophilic granulocytes and neutrophilic granulocytes could be distinguished. At the EM level two granulocyte types were apparent, one with elongated granules containing longitudinal fibrils that consolidated to form an axial rod-like i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
14
1

Year Published

1988
1988
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 15 publications
6
14
1
Order By: Relevance
“…However, such simple lysosome-like granules are common in animal cells and are therefore of no phylogenetic significance. The smaller, lucent granules of Hydrolagus type I granulocytes are similar to spherical cells with lucent cores in Etmopterus baxteri, but no tubular elements were observed in the latter (Hine & Wain 1987a). The rod-like inclusions in Rhinochimaera granules are similar to those of type III granules of lamprey granulocytes (Page & Rowley 1983) and Catostomus commersonii neutrophils (Lester & Desser 1975), but were rarely observed and too poorly characterised to deduce strict homology.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…However, such simple lysosome-like granules are common in animal cells and are therefore of no phylogenetic significance. The smaller, lucent granules of Hydrolagus type I granulocytes are similar to spherical cells with lucent cores in Etmopterus baxteri, but no tubular elements were observed in the latter (Hine & Wain 1987a). The rod-like inclusions in Rhinochimaera granules are similar to those of type III granules of lamprey granulocytes (Page & Rowley 1983) and Catostomus commersonii neutrophils (Lester & Desser 1975), but were rarely observed and too poorly characterised to deduce strict homology.…”
Section: Discussionmentioning
confidence: 85%
“…but eosinophils of both species are negative for this enzyme (Hine & Wain 1988). It is therefore concluded that, like elasmobranchs (Hine & Wain 1987a, 1987b, 1987c many of the cells derive from the eosinophil lineage, but only the coarse granulocytes with their morphological, ultrastructural, and tinctorial similarities to eosinophils of higher vertebrates can be given a specific designation.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations